A Bottom-Up Approach to Short-Term Immersion in Subsistence Marketplaces: Methodological and Substantive Lessons on Poverty and the Environment From Tanzania. (December 2016) - Viswanathan, Madhu; Venugopal, Srinivas; Minefee, Ishva; Guest, Jeremy S.; Mariñas, Benito J.; Bauza, Valerie; Valentino, Lauren; Kupaza, Ramadhani; Jones, Maria
We discuss an international immersion research experience conducted by an interdisciplinary team of business and environmental engineering students and faculty in Tanzania. Using this experience as "data, " we bring out methodological and substantive issues in studying the intersection of poverty and the environment. The approach we describe is bottom-up, beginning with micro-level details of life circumstances. Such micro-level details are often the most challenging to learn and the most neglected in terms of informing practice. Our work speaks to a number of issues such as organizing a short research immersion for effectiveness and efficiency, covering different units of analysis in terms of individuals, households, communities, village-level leadership, and the outside ecosystem of organizations using a bottom-up approach, and combining natural science analytical testing with social science to focus on the substantive domains of environments in subsistence contexts.